The Role of Talent Management in the Management of Contemporary Hotels - Agnieszka Knap-Stefaniuk; Wioleta J. Karna (Perspektywy Kultury, 2022)
In the dynamic environment of the tourism industry, especially in hotel management, a properly implemented concept of talent management has a significant impact on attracting, hiring, developing, and maintaining outstanding, talented employees in order to develop long-term. The main goal of the article is to determine the role of talent management in the management of contemporary hotels. Based on numerous sources, the authors argue that the approach to talent management in hotels leads to more effective use of human resources and builds a competitive advantage. In the first part of the article, the authors explain the concepts of talent and talent management and highlight the importance of talent management in human resources management. The next part describes the special role of managers in the process of talent management in hotels. Next, the authors present the employment in the hotel industry in EU countries; in the last part of the article they indicate mistakes and challenges related to the talent management in the hotel industry.